Using gene––environment interactions to target personalized treatment in mood disorder. (January 2011) - Klengel, Torsten; Binder, Elisabeth B
Mood disorders account for a substantial social and financial burden on society. Although considerable efforts to delineate the underlying pathophysiological pathways have been undertaken during the last decades, only very limited progress on diagnostic and treatment algorithms have been achieved. High hopes have been put into genetics research to elucidate the pathogenesis of mood disorders, but so far, only small and inconsistent associations could be reported. Epidemiologic and family studies have always emphasized the importance of environmental factors; especially the impact of childhood trauma in mood disorders and more recently a number of specific gene––environment interactions have been reported. It is thus likely that the combination of a patient''s life history and genetic susceptibility as well as other laboratory markers might provide a better insight into mental diseases and their treatment options. In this article, we discuss the concept of gene––environment interactions in major depression and their putative role in treatment response and personalized therapy.